Evaluation of the Effect of Low-Level Laser Therapy on Salivary Interleukin-1ß Levels in Chronic Periodontitis Patients - Pratap Mane (International Journal of Medical Toxicology and Legal Medicine, 2024)
This study evaluates the effect of low-level laser therapy (LLLT) on salivary IL-1ß levels in chronic periodontitis patients. Patients were divided into two groups: one receiving scaling and root planing (SRP) alone, and the other receiving SRP combined with LLLT. Salivary IL-1ß levels were measured at baseline, 1 week, 1 month, and 3 months post-treatment. The results showed a significant reduction in IL-1ß levels in the LLLT group, suggesting LLLT as a beneficial adjunctive therapy for chronic periodontitis. A randomized controlled trial with 60 chronic periodontitis patients (30-60 years) was conducted. Patients were divided into SRP alone (control) and SRP with LLLT (experimental) groups. LLLT was applied using a diode laser (810 nm, 0.5 W, 4 J/cm²). Saliva samples were collected at baseline, 1 week, 1 month, and 3 months post-treatment. IL-1ß levels were measured using ELISA. Statistical analysis was performed using paired t-tests and ANOVA. The experimental group showed a significant reduction in salivary IL-1ß levels at all follow-up points compared to the control group (p < 0.05). LLLT significantly reduces salivary IL-1ß levels in chronic periodontitis patients, supporting its use as an effective adjunctive therapy to conventional periodontal treatment. Further research is needed to confirm these findings and establish standardized protocols.